A sugar-coated microbial agent for self-healing cracks in concrete. (1st May 2023) - Jiang, Lu; Han, Qiangqiang; Wang, Wenjing; Zhang, Yu; Lu, Wei; Li, Zhu
Abstract: Cracking is a common disease of concrete structures, and the use of microbially induced calcite precipitation (MICP) to repair cracks is a current research focus. The method of preparing microbial self-healing agent by sugar-coated is considered feasible in previous studies, but the influence of changes in external environmental conditions on the crack-healing effect of concrete is unknown. Based on this, the influence of the external environment (curing conditions, external temperature, cracking time, number of freeze-thaw cycles) on the repairing effect of microbial concrete cracks was comprehensively discussed. Then the self-healing effect of microbial concrete was evaluated using the crack width healing percentage method and the average repair width method. The results show that the crack-healing effect of concrete is better under dry wet cycle or immersion curing, and the average repair width is 0.376 mm and 0.340 mm respectively at 28 d. The inhibition of low temperature on bacteria is greater than that of high temperature. The percentage of the number of completely repaired cracks reached 82.1% at 30 °C. At low temperature (10–25 °C), only cracks with width less than 0.25 mm can be repaired. Even concrete 180 days old can self-healing effectively under the right conditions, and the percentage of the number of completely repaired cracks reached 66.7%. The freeze-thaw cycle has no effect on the crack-healing effect of concrete. The percentage of the number of completely repaired cracks (＜0.4 mm) in self-healing concrete reached 89.4% under the dry-wet cycle curing at 30 °C, indicating that the method of preparing microbial self-healing agent by "sugar-coating" is one of the most feasible methods in the existing research. This study provides methods and suggestions for the development of microbial concrete. Highlights: Sugar-coating is an appropriate method for prepare microbial self-healing agent. Expanded perlite is an effective medium for protecting microorganisms. Crack self-healing is most effective at 25–40 °C. The freeze-thaw cycle has no effect on the crack-healing effect of concrete.